Digital audio watermarking; techniques and applications - Olanweraju, Rashidah Funke; Khalifa, Othman Omran (2012)

(untitled)
Counterfeiting and piracy of intellectual properties are often pointed to as an indispensable problems across the globe, though more intense in some region than others. Currently over millions of digital audio files like digital songs are copied illegally during file-sharing over the networks, costing loss of revenue to the music and broadcasting industries. Right owners such artists, composers, and producers have been searching for ways to protect their creations, discoveries and inventions. These challenges prompted significant research in Digital Watermarking (DW) to develop efficient methods to protect copyright and authentication messages in digital audio in order to prevent forgery and impersonation. This paper brings to view techniques and applications of digital audio watermarking signals. Requirements and Methods of audio watermark were indentified and classified accordingly. A new intelligent audio watermarking technique in a combine domain is proposed to complement the current methods. It is expected that this paper will serve as a launch pad for researchers interested in audio watermarking.